Studies on the performance of artificially submerged waterjet / Fazilah Abdul Aziz and Syarmela Alauldin - Abdul Aziz, Fazilah; Alauldin, Syarmela (1999)
The primary purpose of this project is to build up a in house test rig to get it ready to make an analysis on the artificially submerged cavitating water-jet. It also can be used for other researchers to continue the study in artificially submerged waterjet. The details of the artificially submerged cavitating waterjet test rig are reported. The test rig that has been designed helps in finding the mass loss from the aluminium specimen plate due to cavitation erosion. This work reports how the chamber can facilitate the formation of an artificially submerged cavitating waterjet. The specimen preparation, the experimental set-up and test condition are reported. We are using three methods in doing our analysis, which are weighing the specimen by electronic balance, use Quick Vision machine and Scanning Electron Microscope. The mass loss calculated through the theoretical method is compared with that obtained through the experimental method. And we see a good correlation between the two. This model can be used to predict the mass loss of any ship hull material.